Non-catalytic ozonation of palm oil mill effluent (POME) - Al-Amshawee, Sajjad; R. M., Yunus; Lynam, Joan G. (Elsevier Ltd, 2021)
Ozonation is recognized as an effective treatment to eliminate complex contaminants in wastewater. So far, past studies often applied ozonation for minutes or a few hours. These studies contradict each other in their findings about the ability of ozone to remove inorganics and organics. The present study, for the first time, applied ozone oxidation at doses of 15 and 30 mg/L for a long duration of 144 h to process high-strength wastewater, palm oil mill effluent. Both doses effectively dissolved non-biodegradable solids, ultimately enhancing toxicity removal. However, the 15 mg/L dose resulted in a slower start-up, instability in treatment, and lower solid degradation than the 30 mg/L dose because it was inadequate to abate influent pollutants. The undesirable results of the 15 mg/L dose demonstrated the need for a higher dosage of ozone to result in a higher rate of conversion of solids into biodegradable and dissolved solids over a shorter period of time. The high ozone dose (30 mg/L) demonstrated better startup, more stable performance, and higher final effluent quality than the low ozone dose (15 mg/L). The high ozone dose continued to deliver high-performance treatment over the duration of the study compared to the low ozone dose. During ozonation, particulate matter foams were detected on the surface due to aggregation of solids.